Design of a low dropout voltage regulator (ldo) for wireless sensor nodes - Lee, Hong Ze (2017)
A low dropout voltage regulator for wireless sensor nodes is proposed such that it provides a fixed output voltage of 0.6V irrespective of the load under a supply voltage of 0.9V. It can drive loads ranging from 10μA to 10mA with an output capacitor of 50 pF. It is independent of temperature owing to the embedded voltage reference derived from a bandgap circuit in current mode. Using 0.18μm CMOS technology, all MOSFETs are operating in sub-threshold region at room temperature except the error amplifier. The LDO exhibits a quiescent current of 13.61 μA, a temperature coefficient of 6.86 ppm/°C, a line regulation of 63.62 mV/V and a load regulation of 0.2824 mV/mA at steady state, while providing a power supply rejection ratio of 24.07 dB at the output.